URGENSI REGULASI PENATAAN RUANG DALAM RANGKA PERWUJUDAN PEMBANGUNAN BERKELANJUTAN DI INDONESIA - Janpatar Simamora; Andrie Gusti Ari Sarjono (Nommensen Journal of Legal Opinion, 2022)
Currently, spatial planning has been placed as one of the important components that will determine the success or failure of the development process of a region, especially in the context of the sustainable development process. On the other hand, population growth that is increasingly rapid from time to time ultimately creates an obligation for the government to regulate various facilities for the needs of human life. Through research conducted in a normative juridical manner, the research shows that spatial planning policy is one of the efforts in the context of realizing sustainable development. In line with that, the existence of law in any spatial planning will greatly determine the success or failure of the spatial planning policy itself. The urgency of spatial planning must be interpreted as the main agenda in the context of planning the development of a country or region. Spatial planning will greatly determine the progress of the development of a region. Thus, spatial planning policy must be seen as an instrument that can direct and build humans towards a better civilization in the future.